Pharmacodynamic Evaluation of Dosing, Bacterial Kill, and Resistance Suppression for Zoliflodacin Against Neisseria gonorrhoeae in a Dynamic Hollow Fiber Infection Model - Jacobsson, Susanne; Golparian, Daniel; Oxelbark, Joakim; Alirol, Emilie; Franceschi, Francois; Gustafsson, Tomas N.; Brown, David; Louie, Arnold; Drusano, George; Unemo, Magnus (Frontiers in Pharmacology, 2021)
Antimicrobial resistance in Neisseria gonorrhoeae is threatening the treatment and control of gonorrhea globally, and new treatment options are imperative. Utilizing our dynamic in vitro Hollow Fiber Infection Model (HFIM), we examined the pharmacodynamics of the first-in-class spiropyrimidinetrione (DNA gyrase B inhibitors), zoliflodacin, against the N. gonorrhoeae reference strains WHO F (susceptible to all relevant antimicrobials) and WHO X (extensively-drug resistant, including resistance to ceftriaxone) over 7 days. Dose-range experiments with both strains, simulating zoliflodacin single oral dose regimens of 0.5-8 g, and dose-fractionation experiments with WHO X, simulating zoliflodacin oral dose therapy with 1-4 g administered as q12 h and q8 h for 24 h, were performed. A kill-rate constant that reflected a rapid bacterial kill during the first 6.5 h for both strains and all zoliflodacin doses was identified. In the dose-range experiments, the zoliflodacin 2-8 g single-dose treatments successfully eradicated both WHO strains and resistance to zoliflodacin was not observed. However, zoliflodacin as a single 0.5 g dose failed to eradicate both WHO strains and a 1 g single dose failed to eradicate WHO X in one of two experiments. The zoliflodacin 1 g/day regimen also failed to eradicate WHO X when administered as 2 and 3 divided doses given q12 h and q8 h in the dose-fractionations study. All failed regimens selected for zoliflodacin-resistant mutants. In conclusion, these data demonstrate that zoliflodacin should be administered at >2 g as a single oral dose, to provide effective killing and resistance suppression of N. gonorrhoeae. Future studies providing zoliflodacin pharmacokinetic data for zoliflodacin (and other gonorrhea therapeutic antimicrobials) in urogenital and extragenital infection sites, particularly in the pharynx, and evaluation of gonococcal strains with different gyrB mutations would be important.